UPAYA PENINGKATAN KOMPETENSI GURU DALAM MEMANFAATKAN MEDIA PEMBELAJARAN BERBENTUK POWER POINT MELALUI IHT DI SD NEGERI 45 SUNGAI RAYA KABUPATEN KUBU RAYA - Zaini, Zaini (Universitas Tanjungpura, 2022)
This study aimed to analyze the improvement of teacher competence in utilizing learning media in the form of power points through IHT at SDN 45 Sungai Raya. The research method used in this research is the descriptive method. The subjects of this study were the principal as a researcher and the teacher as a research subject, amounting 8 people. The IHT implementation research procedure is carried out through four stages: a) planning, b) implementation, c) reflection, and d) evaluation. Data collection techniques used are direct observation and documentation techniques, with data collection tools in the form of observation sheets. The results showed increased teacher competence in utilizing learning media in the form of PowerPoint through IHT in cycle I (64.84%) and cycle II (84.89%). Overall, teachers can explain the benefits of information technology about increasing student creativity, teachers can explain how to make PowerPoint, teachers can earn power points as teaching materials in class, and teachers can use PowerPoint applications in learning, thereby increasing motivation for student learning and student learning outcomes, stimulating children to find out more information about the teaching materials presented.